Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/2314759
|View full text |Cite
|
Sign up to set email alerts
|

Ferulated Arabinoxylans and Their Gels: Functional Properties and Potential Application as Antioxidant and Anticancer Agent

Abstract: In the last years, biomedical research has focused its efforts in the development of new oral delivery systems for the treatment of different diseases. Ferulated arabinoxylans are polysaccharides from cereals that have been gaining attention in the pharmaceutical field due to their prebiotic, antioxidant, and anticancer properties. The antioxidant and anticancer properties of these polysaccharides make them attractive compounds for the treatment of cancer, particularly colon cancer. In addition, ferulated arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 118 publications
(211 reference statements)
2
70
0
7
Order By: Relevance
“…Thus, materials with smaller pores will have a higher loading capacity in a lower volume of material . Considering the application of AX gels as encapsulating agents, the development of AX gels with a highly crosslinked network and smaller pores could improve the loading capacity of the gels, provide a better encapsulation of biomolecules and ensure its release in the target site . Thus, a decrease of protein in AX could allow the production of gels with a more compact microstructure by reducing the steric effect between polysaccharide chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, materials with smaller pores will have a higher loading capacity in a lower volume of material . Considering the application of AX gels as encapsulating agents, the development of AX gels with a highly crosslinked network and smaller pores could improve the loading capacity of the gels, provide a better encapsulation of biomolecules and ensure its release in the target site . Thus, a decrease of protein in AX could allow the production of gels with a more compact microstructure by reducing the steric effect between polysaccharide chains.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation of gastrointestinal conditions demonstrated that 76% of the insulin carried is released in the colon, indicating that these gels could be used as an alternative system for the delivery of insulin and probiotics targeted to colon for the treatment of diabetes . Considering that AX gels can be degraded by the colonic microbiota and exhibit antioxidant activity, they could be considered as an excellent alternative for the development of colon‐targeted drug delivery systems for the treatment of diseases such as diabetes and colon cancer …”
Section: Introductionmentioning
confidence: 99%
“…Dominating dimers of ferulic acids in cross-linked fibrex gel were 8-O-4 and 8-5 , which increased after gel formation [29]. Recently, formation of cross-links of ferulic acid of higher molecular masses than dimers and undefined superior structures was also reported [25].…”
Section: Identifying Diferulic Acids In Cross-linked Fibrex Gelmentioning
confidence: 93%
“…Subsequently, two phenoxy or alkoxy radicals cross-link, and the coupling of the unpaired electrons forms a new covalent bond that connects two sugar chains. Consequently, the structure of the dimers formed during gelation depends on the radical position [13,25].…”
Section: Identifying Diferulic Acids In Cross-linked Fibrex Gelmentioning
confidence: 99%
See 1 more Smart Citation